‘To Proclaim Liberty to the Captives’: Matthew 11.28–30 in the Light of ot Prophetic Expectation - Charette, B. (New Testament studies, 1992)
The description of Wisdom in Sirach has exercised a profound influence on the interpretation of Matt 11.28–30. Many scholars, impressed with the evident parallels between Sir 51.23–7; 6.23–31 and the Matthean logion,1 have regarded the latter as dependent on the former.2 Others, taking a further step, have felt justified in interpreting the logion with reference to a wisdom christology. According to this view, Jesus, represented as Wisdom incarnate,3 offers rest to those burdened by the legal interpretations of the Pharisees4 through his yoke, which stands for his teaching, or, more precisely, for his interpretation of the law.5 This approach to the logion has had its detractors,6 and some scholars have questioned the suitability of positing any connection between Sirach and the logion.7 It is not the purpose of the present discussion to enter into this debate, but rather to draw attention to what might be termed a neglected feature in the discussion of Matt 11.28–30, namely the relation of the logion to certain OT prophetic themes.8